1999
DOI: 10.1152/ajpheart.1999.277.3.h1207
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-reperfusion rapidly increases COX-2 expression in piglet cerebral arteries

Abstract: In the newborn, cyclooxygenase (COX)-derived products play an important role in the cerebrovascular dysfunction after ischemia-reperfusion (I/R). We examined effects of I/R on expression of COX-1 and COX-2 isoforms in large cerebral arteries of anesthetized piglets. The circle of Willis, the basilar, and the middle cerebral arteries were collected from piglets at 0.5–12 h after global ischemia (2.5–10 min, n = 50), hypoxia ( n = 3), or hypercapnia ( n = 2) and from time-control ( n = 19) or untreated animals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 32 publications
4
32
0
3
Order By: Relevance
“…In our model of restraint stress, we have shown that activation of COX-2 precedes NOS-2 probably because, although protein synthesis is required in both cases, COX-2 remains constitutively expressed in the brain (Yamagata et al, 1993). The relations between these two sources of oxidative status are consistent with the fact that, as observed also in brain ischemia, COX-2 is expressed before NOS-2 (6 and 12 h, respectively, after transient occlusion of the MCA) (Nogawa et al, 1998) and 30 min to 2 h after reperfusion (Domoki et al, 1999). On the other hand, these data strongly suggest that both enzymes work in the same direction to produce oxidative status in acute stress.…”
Section: Discussionsupporting
confidence: 77%
“…In our model of restraint stress, we have shown that activation of COX-2 precedes NOS-2 probably because, although protein synthesis is required in both cases, COX-2 remains constitutively expressed in the brain (Yamagata et al, 1993). The relations between these two sources of oxidative status are consistent with the fact that, as observed also in brain ischemia, COX-2 is expressed before NOS-2 (6 and 12 h, respectively, after transient occlusion of the MCA) (Nogawa et al, 1998) and 30 min to 2 h after reperfusion (Domoki et al, 1999). On the other hand, these data strongly suggest that both enzymes work in the same direction to produce oxidative status in acute stress.…”
Section: Discussionsupporting
confidence: 77%
“…Although COX-2 is also expressed in response to several physiological stimuli, it is the key molecule in inflammation. COX-2 up-regulation is a hallmark of IRI (10,12). Moreover, many investigators have demonstrated the importance of the blockade of the COX pathway in promoting better organ function in ischemic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Both isoforms, COX-1 and COX-2, participate in the endothelial cell activation that follows IRI (9,10). We have shown that COX blockade in the murine model of IRI leads to better organ function and preserves the parenchymal architecture (11,12).…”
Section: Introductionmentioning
confidence: 98%
“…COX-2 is known to be induced by anoxic stress, parenchymal and cerebrovascular COX-2 mRNA levels were shown to increase within 0.5-2 hours after global cerebral ischemia in the piglet [67,150]. In our study made on acute changes after birth asphyxia, asphyxia was shown to significantly increase the number of damaged neurons after 4 hours, moreover, hydrogen ventilation was shown to partially alleviate the hypoxic/ischemic neuronal damage [141].…”
Section: Map-2 Densitymentioning
confidence: 67%
“…In our laboratory, the newborn piglet model has long been used to study the morphology and functional responses of cerebrovascular system in physiologic and pathologic conditions [61][62][63][64][65][66][67]. We and others have repeatedly shown that hypoxic-ischemic stress in newborn piglets severely attenuated CR to various so called "hypoxia-ischemia sensitive" stimuli determined in pial arterioles 1 hour after the insult [61,64,[68][69][70].…”
Section: Animal Models In Hie Researchmentioning
confidence: 99%